Sound Based Identification of snail Pest in Agriculture - Sneha J, Adeline; Chakravarthi, Rekha; Hisham Khamis, Nor; Harun, Mokhtar; You Kok Yeow, You (International Journal of Engineering and Technology, 2018)
Snails are harmless creatures; however, they can cause heavy losses to the agriculture industry.Â The Giant African snails are the natural enemies for the farmers which could cause massive damages to vegetation. These snails possess high reproductive ability, devouring good quality of meals, loss of quarantine facilities which makes this snail to have detrimental impact in destruction of the fields.Â Â The farmers apply molluscicides of their fields often which will guard the crops from snails. The alternative approach has been practiced with the aid of the farmers are capturing the snails all over the farm and killing it with boiling water. This all happens because of the shortage of initial identity of snails within the fields. This paper describes about the snails affecting the fields and modern-day technology to govern the snail by means of applying molluscicides only to the infected crop now not to the complete area. The suggested acoustic identification identifies the presence of snail with its sounds. The various features of the signals are extracted and the frequency is determined which has been continued with the neural network classification for automatic identification.Â Â Â This technology identifies the snail in its initial stage so that the effective control action has been taken without damaging the environment and field.Â Â